From Punitive Silence to Restorative Codification: A Comparative Analysis of Diversion for Children in Conflict with the Law under the Old Indonesian Criminal Code and Law Number 1 of 2023 - Dhea Aulia Malem Purba; Qori Rizqiah H Kalingga (International Journal of Social Science and Religion (IJSSR), 2026)
Diversion constitutes a mechanism for resolving juvenile criminal cases outside the formal criminal justice process through a restorative justice approach. This article examines the normative transformation of diversion for children in conflict with the law by comparing the old Indonesian Criminal Code with Law Number 1 of 2023 on the Criminal Code. Under the old Criminal Code, diversion was not explicitly regulated, as the code was primarily oriented toward punishment, prosecution, and an adult-centered model of criminal liability. The regulation of diversion was therefore mainly developed through Law Number 11 of 2012 on the Juvenile Criminal Justice System. Law Number 1 of 2023 marks a significant shift by expressly placing diversion, measures, and penalties for children within the general structure of Indonesian criminal law. The new Criminal Code requires diversion to be attempted for offences punishable by imprisonment of less than seven years and that do not constitute recidivism, while also emphasizing non-custodial measures, child rehabilitation, and social reintegration. This development does not replace the Juvenile Criminal Justice System Law but strengthens its restorative logic by embedding child-sensitive principles into the national criminal law framework. The comparison shows a movement from punitive silence toward restorative codification, reflecting Indonesia's broader commitment to child protection, proportional accountability, recovery, and the best interests of children in conflict with the law.